Overview of Leprosy Reactions at Universitas Sumatera Utara Medical Faculty Hospitals between 2017 and 2021 - Lubis, Ramona Dumasari; Yosi, Ariyati (Open Access Macedonian Journal of Medical Sciences, 2024)
BACKGROUND: Leprosy, or Morbus Hansen, is a chronic granulomatous disease caused by Mycobacterium leprae that involves the skin and peripheral nerves, with or without motor disorders. Leprosy reactions are immune-mediated acute or subacute inflammatory episodes that interfere with chronic disease and are classified into three types: type 1 (RR), type 2 (ENL), and the Lucio phenomenon. AIM: The purpose of the study is to describe the epidemiology of leprosy reactions at Universitas Sumatera Utara (USU) teaching hospitals and provide a description of factors associated with the reactions that might provide valuable information for future studies. METHODS: This is a cross-sectional analytic study with total sampling on medical records of patients in the Dermatology and Venereology Polyclinic at H. Adam Malik Hospital Medan and USU Education Hospital in 2017–2021. RESULTS: The incidence of leprosy reactions at the USU Medical Faculty Education Hospital in 2017–2021 was 41 cases. The majority of reaction types were type 2 reactions (68.3%). Risk factors for type 1 reactions were a history of reactions, being elderly, multiple lesions or nerve involvement, and co-infections, whereas the risk factors for type 2 reactions were LL, younger age, bacterial index >4+, stress, and co-infections. The highest age group proportion was 18–59 years (95.1%) and was more common in men (70.7%), which mostly appeared before treatment (39.1%). The incidence of leprosy reactions was 26 new cases per 100 patients. CONCLUSION: The highest proportion of leprosy reactions was type 2, within the adult age group (18–59 years), males, and before treatment.